MAIN DIFFERENCES BETWEEN ONLINE AND OFFLINE LEARNING. RECOMMENDATIONS FOR THE LANGUAGE TEACHERS - Axmedova , Matluba; Odiljonova , Mukhlisa; Nazirova , Zebokhon (Educational Research in Universal Sciences, 2023)
In schools in many countries around the world since the start of the COVID pandemic in 2020 classes have moved to online education as the only method of teaching, and online education has entered the educational process as another form of traditional (offline) education. This article compares online and offline learning in today’s modern world. At the same time, it explores the controversial aspects of online and offline learning. In addition, feedbacks are collected to compare the efficiency between online learning and offline teaching. Factors that influence the efficiency difference are analyzed and suggestions are given for having better studying experience. The differences between offline and online learning are considered and some tips and recommendations for language teachers are given. In addition, several mistakes of teachers during the lesson are mentioned and advice is given to them in this regard.